CULTURAL VALUES OF POLITENESS IN EFL CLASSROOM: A STUDY OF ETNOGRAPHY OF COMMUNICATION - Fitriyah Fitriyah; Emzir Emzir; Sakura Ridwan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
One of the purposes of learning English as a foreign language (EFL) is to be able to communicate. The Students must have communicative competence that does not only consist of linguistic competencies, but also socio-cultural ones. This paper aims to analyse the cultural themes of politeness strategies in EFL Classroom. The research in this paper focused on directive and expressive speech acts in EFL classroom. The participants of this study are three lecturers and the students of three English classes. The data are gathered by video audio by recording the lecturers’ utterances and students’ compliances to the lecturer, in order to find the politeness strategies and the cultural values in EFL classroom. The results show that; 1) There are seven kinds of cultural values of politeness strategies in EFL classroom, such as glorifying God, agreement, apologising, questioning, delivering praise, delivering thank you, and praying for others, 2) The lecturers and students dominantly use agreement and questioning in EFL Classroom. Thereby, this issue is relevant to EFL classes focusing on the improvement of both lecturers and students’ language and cultural skill. The analytical tool refers to the theories of Brown and Levinson’s positive and negative politeness, and the ethnography of communication method. The findings of this study will probably give insights into the pragmatic and conversational rules of EFL. The last part of this paper aims at summarizing that the implications that this paper are relevant to the strategies of teaching English as a Foreign Language.